PENGARUH BUDAYA KONSUMTIF SEBAGAI PEMICU TINDAK KORUPSI DALAM PERSPEKTIF EKONOMI ISLAM - Saadah, Ani; Sudrajat, Adit Rizki; Masti, Indri; Azzahwa, Yuki Wulan; Hamidah, Mutiara; Fajrussalam, Hisny (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2025)
Abstract : This study examines the impact of consumptive culture as a trigger for corruption in the perspective of Islamic economics. This research is motivated by the increasing consumptive trend among university students, which has the potential to encourage individuals to engage in unethical financial behavior, including corruption. This research uses a mixed methods approach, which combines a quantitative survey and a qualitative Systematic Literature Review (SLR). Data was collected from 50 students at Universitas Pendidikan Indonesia, Purwakarta Campus, aged 18-25 years. The results showed that high social pressure and expectations of a luxurious lifestyle can encourage individuals to seek shortcuts, including through acts of corruption. In the perspective of Islamic economics, consumptive behavior has a significant influence on corruption. This is evidenced by 37 out of 50 respondents agreeing that Islamic economic principles can help reduce consumptive culture and prevent corruption. By applying Islamic economic values such as honesty, trustworthiness, and transparency, excessive consumptive behavior can be controlled so that the potential for corruption can be minimized. This research confirms the importance of Islamic economic education in shaping students' financial awareness and ethics to prevent corrupt practices from an early age. Keywords: Consumptive, corruption, Islamic economics, financial ethics, student ethics.